2009
DOI: 10.1177/003172170909100307
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Teaching Gap

Abstract: Although the policy context that surrounds education changes like a series of hurricanes blowing across the Gulf of Mexico, the substantive nature of what happens in classrooms stays pretty much the same. In fact, this is what we would have predicted if teaching is a cultural activity, and after years of studying teaching here and elsewhere, we are convinced, more than ever, that it is. Our book, The Teaching Gap, which was published in 1999, was primarily a report covering a large research project, the TIMSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
290
0
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(317 citation statements)
references
References 0 publications
7
290
0
20
Order By: Relevance
“…It is at this stage of life that the role of the school, the school's teacher or the school's psychologist should be strengthened. Too difficult, but necessary to have a civilized and less violent society (Stigler & Hiebert, 1999). Also, according to Sigmund Freud, it is shown that wrong actions have a hidden motivation, and therefore psychoanalysis is used to pave the way for the recognition of this motivation (Dibra, Hida, & Gjikondi, n.d., p.271).…”
Section: Factors Affecting Violent Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is at this stage of life that the role of the school, the school's teacher or the school's psychologist should be strengthened. Too difficult, but necessary to have a civilized and less violent society (Stigler & Hiebert, 1999). Also, according to Sigmund Freud, it is shown that wrong actions have a hidden motivation, and therefore psychoanalysis is used to pave the way for the recognition of this motivation (Dibra, Hida, & Gjikondi, n.d., p.271).…”
Section: Factors Affecting Violent Behaviorsmentioning
confidence: 99%
“…However, a profession is not created by certifications but by the existence of sufficient professional knowledge, the existence of a mechanism to improve it and the true desire of members of this profession to improve their practice (Stigler & Hiebert, 1999). Teachers should not only be trained for specific topics, but at the same time associate their work with the desire to be more effective in their noble mission of generations' education.…”
Section: No Answermentioning
confidence: 99%
“…The mathematical understandings of such teachers, the meanings they make of mathematics in their university setting, form the basis of their future teaching, both in terms of their concepts of mathematics and also their philosophy in developing their students' understandings. If they have been enculturated into seeing teaching as a process of transmitting knowledge, then their own teaching is most likely also to take this form (Lortie 1975;Romberg and Carpenter 1986;Stigler and Hiebert 1999).…”
Section: Mathematics Teaching At the University Levelmentioning
confidence: 99%
“…In fact, early efforts to systematically study and compare classroom practices across nations and cultures, such as the TIMSS video study (e.g. Stigler and Hiebert 1999), were spurred by the differences found in students' response to international surveys like TIMSS. This led to a growing interest in the cultural and institutional conditions for mathematics teachers' practice and knowledge in East Asia, and more broadly to research seeking to make sense of what Stigler and Hiebert (op.…”
Section: Introductionmentioning
confidence: 99%